خصوصية عقد العمل تحت التجربة في قانون العمل الجزائري - زوبة, عزالدين (جامعة الوادي University of Eloued, 2019)
إن الطبيعة القانونية الخاصة لعقد العمل تحت التجربة كان لها أثر واضح بالنسبة إلى القواعد غير المألوفة التي وضعها المشرع الجزائري لتنظيم أحكامه، حيث انعكست هذه الاخيرة على المركز القانوني للعامل أثناء فترة التجربة. اعتبر المشرع كقاعدة أن اللجوء الى فترة التجربة أمر جوازي، اذ يعتبر هذا الشرط مقررا لمصلحة طرفيه. يبدأ سريان مدة التجربة من تاريخ تنصيب العامل وشروعه في مباشرة العمل الموكل اليه فعلا وليس من تاريخ ابرام أو انعقاد العقد، ولا يجوز وفقا للقضاء ابرام أكثر من عقد عمل تحت التجربة مع نفس صاحب العمل، اذ يشترط لإجراء فترة التجربة أن يكون العامل مشغلا في المنصب لأول مرة. لم يوجب المشرع الشكلية في فترة التجربة وبذلك يمكن إثباتها بمختلف وسائل الإثبات اذ يتمتع العامل أثناءها بنفس الحقوق والواجبات التي يتمتع بها العامل في عقد العمل البات باستثناء الاستفادة من بعض الوضعيات أو حالات تعليق علاقة العمل. أعطى المشرع السلطة الكاملة لصاحب العمل في إنهاء عقد العمل تحت التجربة دون تبرير، اذ لم يشترط على هذا الأخير اثبات عدم صلاحية العامل لإمكانية إنهاء هذا العقد كما أعفاه من الإشعار المسبق والتعويض عند ممارسة حقه في الفسخ، فقيده فقط بضرورة استعمال هذا الحق أثناء سريان فترة التجربة وقبل انقضائها. The trial period is necessary for both parties (the employer and the employee), it allows one side to the employer to assess and test the skills of the "new" employee in his "new" position. On the other hand, the employee judges during this period the operation of the company to decide if it suits him. The special legal nature of the employment contract during the probationary period prompted the legislator to make special provisions that had a profound impact on the worker's legal status during this period. The probation period thus constitutes a first phase of the employment contract, it is not mandatory and must, to exist, be provided for in the employment contract or the collective agreement. The maximum duration of this period is fixed by the Labor Code, the collective agreements or the contract of employment. It is defined as "the period during which each of the parties may voluntarily terminate the employment contract without notice or compensation". In this spirit, we have tried to answer the following problem: does the legal status of the worker on probation guarantee him adequate protection against the arbitrariness of the employer?.
The Specificity Of The Contract Of Employment During The Trial Period In Algerian Labor Law
Keywords: عقد العمل، فترة التجربة، عامل، حماية، حقوق، تعسف; Labor contract, trial period, worker, protection, rights, abuse